2009
DOI: 10.1364/ao.48.000e13
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable and adaptive photonic networks for high-performance computing systems

Abstract: As feature sizes decrease to the submicrometer regime and clock rates increase to the multigigahertz range, the limited bandwidth at higher bit rates and longer communication distances in electrical interconnects will create a major bandwidth imbalance in future high-performance computing (HPC) systems. We explore the application of an optoelectronic interconnect for the design of flexible, high-bandwidth, reconfigurable and adaptive interconnection architectures for chip-to-chip and board-to-board HPC systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Inherent features of optical components make them ideal for transferring planes comprising millions of data points simultaneously and thus achieving effective multi-dimensional input/output and parallel processing at the same time. [3]- [12]. The optical bi-stabilities recently developed with switching times in the order of Femtoseconds [13], FS, compared with milliseconds in electronics, have increased the possibility of using optics for the practical realization of new parallel optical computers for optical information processing especially in the field of Knowledge base systems (KBSs) and text mining as they have reached the Terabyte level [14].…”
Section: Introductionmentioning
confidence: 99%
“…Inherent features of optical components make them ideal for transferring planes comprising millions of data points simultaneously and thus achieving effective multi-dimensional input/output and parallel processing at the same time. [3]- [12]. The optical bi-stabilities recently developed with switching times in the order of Femtoseconds [13], FS, compared with milliseconds in electronics, have increased the possibility of using optics for the practical realization of new parallel optical computers for optical information processing especially in the field of Knowledge base systems (KBSs) and text mining as they have reached the Terabyte level [14].…”
Section: Introductionmentioning
confidence: 99%
“…40 Recently, Kodi and Louri have demonstrated that optical based system architecture shows better performance than electrical interconnects for uniform and nonuniform patterns without the application of reconfiguration techniques. 41 Even with the application of reconfiguration techniques, the dynamically reconfigurable optoelectronics provides much better performance for all communication patterns. Caulfield et al 42 have also proposed an electro-optical logic system with silicon-oninsulator ͑SOI͒ resonant structures.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have suggested optics as a complementary technology for breaking major performance barriers faced by conventional electronic technologies. Therefore optical algebraic computers have become extremely popular [1][2][3][4][5][6][7]. Inherent features of optical components make them ideal for transferring planes comprising millions of data points simultaneously achieving effective multi-dimensional input/output and parallel processing.…”
Section: Introductionmentioning
confidence: 99%